The Changing Perceptions of Gender Equality in Media and Popular Culture - Arianto, Shakira Dwi Azura; Al Ramadhan, Muhammad Fakhran (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This journal explores the evolving perceptions of gender equality in media and popular culture, examining how various forms of representation have influenced societal attitudes toward gender roles over time. By analyzing of media from films, also from survey to various groups of ages. this study investigates how narratives surrounding gender equality have shifted in response to cultural, social, and political movements.Key themes include the portrayal of strong female characters, the deconstruction of traditional masculinity, and the intersectionality of race, class, and sexuality within gender discourse. Ultimately, this study aims to contribute to the exploration of the evolving perceptions of gender equality in media and popular culture.